Pressure and microwave sensors/actuators based on smart hydrogel/conductive polymer nanocomposite - Rivero, Rebeca Edith (2013)
A nanocomposite is fabricated by formation of a conductive polymer, using in situ oxidative polymerization, inside a thermosensitive crosslinked hydrogel. FE-SEM micrographs show the nanometric domains of the conductive material (polyaniline, PANI) dispersed in the hydrogel matrix based on cross linked poly(N-isopropylacrylamide) (PNIPAm). The thermosensitive properties of PNIPAm and copolymers with 2-acrylamido-2-methyl propane sulfonic acid (AMPS) are not affected by the presence of conductive polymer nanoparticles. The incorporation of PANI improves the mechanical properties of the hydrogel allowing it to swell up to 30,000% without breaking. Since the conductive polymer absorbs strongly microwave radiation at pH < 4 and heats up, the nanocomposite containing PANI suffer phase transition upon microwave irradiation. At pH > 4, PANI is not conductive and the nanocomposite becomes insensitive to microwaves. However, using a pH insensitive conductive polymer (polypyrrole, PPy) in the nanocomposite makes it sensitive to microwaves at all pH values. The nanocomposite is used in a chemomechanical actuator where drug release is driven remotely by microwave irradiation. Since the PNIPAm-co-2%AMPS/PANI nanocomposite is soft and electronically conductive, could be used as pressure/force sensor. It is shown that a compressive force applied on a cylinder of that nanocomposite increases the conductivity of material. Additionally a switch is built which turns off upon microwave irradiation. Therefore, the nanocomposites are potential candidates for different technological applications, such as: a force/pressure electrical sensor, a drug delivery device driven remotely by microwaves, pH or temperature electrical switches and an electric switch driven by microwaves.